Primitive Vascular Plants and Microfossils from the Río Seco de los Castaños Formation, San Rafael Block, Mendoza Province, Argentina - Morel, Eduardo Manuel (2017)
In this contribution we describe fossil plant remains from Río Seco de los Castaños Formation, at San Rafael Block, Mendoza Province, Argentina. The fossil plants comprise non-forked and forked axes without or with delicate lateral expansions, which are assigned to Bowerophylloides cf. mendozaensis and Hostinella sp. We refer them to primitive land plants and discuss about their systematic affiliation. Furthermore, we mention the presence of a diverse acritarch assemblage present in the same lithostratigraphic unit. On the basis of the taxonomical information and stratigraphic correlation, we could infer that Río Seco de los Castaños Formation has an Early Devonian age. The taphonomical conditions of this fossil association would indicate that the plants were transported some distance from their presumed coastal and riverbank habitats. Finally, studying the amount and the percentage of kaolinite within charcoal levels, warm to cool temperate paleoclimatic conditions were deduced.